An Iranian experience on renal allograft diseases* - Taheri, Diana (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: Renal transplantation is the treatment of choice for most patients with end stage renal disease. In addition, renal biopsy is the gold standard to assess the causes of renal allograft dysfunction. This study was designed to evaluate and designate renal lesions according to Banff schema. METHODS: In this cross-sectional study, all renal allograft biopsies obtained from renal transplant patients at Alzahra and Noor referral hospitals in Isfahan during 2006-2008 were studied. Evaluations were made according to the Banff classification 2009. Clinical data was collected from the pathology database and analyzed using SPSS. RESULTS: A total number of 161 specimens were studied from 68% male and 32% female subjects. The donor source was living unrelated in 85%, living related 9.9% and cadaveric in 5% of cases. Pathologic results showed 22.4% acute tubular necrosis (ATN), 13.7% interstitial fibrosis and tubular atrophy (IF/TA) grade II, 9.9% IF/TA (Grade III), 6.8% acute T-cell mediated rejection (TCMR-IA), 5.6% TCMR-IB, 5% borderline change, 5% infarction, 4.3% TCMR-IIA, 4.3% TA/IF (Grade I), 3.7% acute antibody-mediated rejection (ABMR), 1.9% TCMR-IIB and 17.4% other lesions. CONCLUSIONS: The commonest causes of graft dysfunction after kidney transplant were IF/TA, no evidence of any specific etiology (NOS) and ATN. Living donors were found to be important sources for kidney transplantation in Iran.